Prediction of Henry's Law Constants on the Basis of the Corresponding States Theorem - V.V. Kutarov; B.M. Kats (Adsorption Science & Technology)
It has been suggested that the well-known two-parameter Corresponding States Theorem for the prediction of the Henry coefficient should be broadened to the four-parameter theorem. The corresponding four-parameter theorem was used to analyze the experimental data for the adsorption of 16 organic and non-organic substances onto active carbon of the Kureha beads type. Employing this theorem to account for the form and change in position of the minimum in the potential curve, it was shown that the Corresponding States Theorem could be applied for the prediction of the Henry coefficient for molecules of arbitrary configuration under conditions requiring the introduction of quantum amendments. All the suggested amendments to the known two-parameter Corresponding States Theorem were strictly based and could be easily defined a priori.